Lucini ésotérique et vers-libriste : une interprétation cabaliste et prospective des Armonie sinfoniche (ENTHYMEMA, 2022)
The Symphonic Harmonies  are a composite project probably prepared by G. P. Lucini between 1885 and 1888 of which only two poems were published in 1892, those ones that show Lucini’s first verslibrist attempt. These two poems mark the beginning of an experimentation that will be typical of the symbolist and ‘futurist’ poetry of Lucini, who rightfully will be later considered as the inventor of the free verse in Italy, thanks to a revival accomplished by the Italian neo-avant-gardists of the 60’s. Some other parties of his early project, which remained unpublished during his lifetime, show his interests in cabalism. Without underestimating the contributions of the 70’s on this subject, we will propose its possible sources and a more profound esoteric interpretation of these writings, which will also be considered in relation to Lucini’s concurrent and future production.
Keywords: Esotericism; Symbolism; Free verse; Lucini; Symphonic Harmonies